Modified biological filler, preparation method and application thereof
By introducing MgFe-LDHs, SA and PVA on the surface of the ceramate, a three-dimensional hydrophilic gel-like polymer is formed, which solves the problems of small specific surface area, insufficient mechanical strength and limited total nitrogen removal capacity of traditional ceramate biofillers, and achieves more efficient pollutant removal and stability of biofillers.
Patent Information
- Application Number
- CN202411417670.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-10-11
AI Technical Summary
Traditional ceramic biofillers have problems such as small specific surface area, insufficient mechanical strength, low biodegradation efficiency and limited ability to remove total nitrogen.
Modified biofillers were prepared by introducing MgFe-LDHs, SA and PVA on the surface of the ceramate to form a three-dimensional hydrophilic gel-like polymer. The method includes co-precipitation method to prepare MgFe-LDHs powder and to form a gel-like polymer with SA and PVA on the surface of the ceramide by cross-linking reaction.
Modified biofillers significantly increase the surface area, enhance the biofilm formation ability, improve the pollutant removal efficiency, especially show superior effects in the removal of total nitrogen, and have stronger mechanical and chemical stability.
Smart Images

Figure CN118993320B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of landfill leachate wastewater treatment, and specifically relates to a modified biological filler, and a preparation method and application thereof. Background Art
[0002] Leachate is a complex organic wastewater produced in the process of urban sanitary landfill. It contains high concentrations of difficult-to-degrade organic matter, total nitrogen, inorganic salts and various suspended solids, which can pose serious hazards to human health and the ecological environment. Therefore, proper treatment of leachate is of vital importance.
[0003] At present, the treatment technologies for landfill leachate include advanced oxidation technology or a combination of advanced oxidation technology and biological treatment technology. As a synergistic treatment technology combining advanced oxidation technology and biological treatment technology, the non-membrane process of Fenton oxidation + BAF biofilter has the advantages of low energy consumption, easy management, easy control, and few external passive control conditions, so as to ensure that the effluent water quality standards are met under different influent water quality conditions and realize the full quantitative treatment of landfill leachate.
[0004] As an important treatment unit of this process, the treatment efficiency of BAF biofilter is correlated with the performance of biological fillers. Traditional fillers such as expanded clay have the following main problems: first, the small specific surface area of expanded clay will limit the adhesion ability of microorganisms and biodegradation efficiency; second, the mechanical strength of expanded clay will be broken during the process of water flow and backwashing, resulting in fine particles, which will affect the water quality and the filtration effect of the biofilter; third, the initial biofilm hanging time of expanded clay may be long, and the biofilter needs a long time to achieve a stable treatment effect, that is, the treatment cycle is long; fourth, when the water quality fluctuates, expanded clay will greatly affect the treatment efficiency of the biofilter. Summary of the invention
[0005] The purpose of the present invention is to use ceramsite as a carrier and introduce a variety of functional materials to form a three-dimensional hydrophilic gel polymer on the surface of ceramsite to obtain a modified biological filler, so as to solve the technical problems of existing biological fillers such as low specific surface area, lack of biocompatibility, insufficient mechanical strength and limited total nitrogen removal capacity.
[0006] In order to achieve the above object, the present invention provides a method for preparing a modified biological filler, the preparation method comprising the following steps:
[0007] Step 1), preparing MgFe-LDHs powder by coprecipitation method;
[0008] Step 2), adding the MgFe-LDHs powder to the PVA-SA mixed solution under stirring and at a preset temperature, and stirring for a first preset time to obtain a MgFe-LDHs-SA-PVA mixed solution;
[0009] Step 3), immersing the ceramsite in the MgFe-LDHs-SA-PVA mixed solution for 8h to 12h to obtain immersed ceramsite, wherein the mass volume ratio of the ceramsite to the MgFe-LDHs-SA-PVA mixed solution is: 1g: (2-5)ml;
[0010] Step 4), immersing the immersed ceramsite in a supersaturated boric acid solution containing CaCl2 and NaCl, so that the calcium chloride and SA, and the boric acid and PVA respectively undergo cross-linking reactions, and after the cross-linking reaction is completed, continuing to soak the ceramsite for a second preset time, and after washing, obtaining MgFe-LDHs-SA-PVA composite ceramsite, wherein the MgFe-LDHs-SA-PVA composite ceramsite is a modified biological filler for adsorbing ammonia nitrogen.
[0011] In a specific embodiment, the step 1) comprises:
[0012] Step (a), under stirring, respectively adding a first solution and a second solution to deionized water, and controlling the reaction temperature to be 70°C to 80°C, and the pH value to be 9.8 to 10.2, wherein the first solution comprises a magnesium salt and an iron salt, and the molar ratio of magnesium ions to iron ions is 2:(1 to 1.25), and the solute in the second solution is sodium hydroxide and sodium carbonate, wherein the molar concentration ratio of metal ions in the first solution, hydroxide ions in the second solution, and carbonate ions in the second solution is (0.3 to 0.4):(1.8 to 2.2):(0.04 to 0.06).
[0013] After the step (b), the dropwise addition is completed, and the aging is continued at 70° C. to 80° C. for 24 h to 30 h. The suspension obtained by aging is filtered, washed, dried, and ground to obtain MgFe-LDHs powder.
[0014] In a specific embodiment, in step (b), the drying conditions include: a drying temperature of 80° C. to 100° C., and a drying time of 18 h to 24 h.
[0015] In a specific embodiment, in step 2), the preset temperature is 80°C to 90°C.
[0016] In a specific embodiment, in step 2), the mass ratio of MgFe-LDHs, PVA and SA in the MgFe-LDHs-SA-PVA mixed solution is: (3-7.5): (3-5): (1-2).
[0017] In a specific embodiment, in step 2), the PVA-SA mixed solution is prepared by the following method: sodium alginate is added to a polyvinyl alcohol solution, wherein the amount of sodium alginate added is 1wt% to 2wt% based on the mass of the polyvinyl alcohol solution, and the mass percentage of polyvinyl alcohol in the PVA-SA mixed solution is 3wt% to 5wt% based on the mass of the PVA-SA mixed solution; wherein the degree of polymerization of polyvinyl alcohol in the polyvinyl alcohol solution is 100,000 to 150,000.
[0018] In a specific implementation, in step 2), the first preset time is 8 hours to 12 hours, and in step 4), the second preset time is 2 hours to 4 hours.
[0019] In a specific embodiment, in step 4), based on the mass of the supersaturated boric acid solution being 100%, the mass percentage of the calcium chloride is 5wt% to 7.5wt%, and the mass percentage of the sodium chloride is 0.5wt% to 1wt%.
[0020] The present invention also provides a modified biological filler, which is prepared by the preparation method of the modified biological filler described above.
[0021] In the present invention, the biological filler includes ceramsite and a three-dimensional hydrophilic gel polymer formed on the surface of the ceramsite by MgFe-LDHs, SA and PVA.
[0022] The present invention also provides the use of the modified biological filler prepared by the preparation method of the modified biological filler described above in wastewater treatment.
[0023] Preferably, the modified raw filler is used in a BAF biofilter to treat wastewater.
[0024] The beneficial effects of the present invention include at least:
[0025] 1. The modified biological filler (MgFe-LDHs-SA-PVA composite ceramsite) provided by the present invention uses traditional ceramsite as a carrier, and through a cross-linking reaction, MgFe-LDHs, SA (sodium alginate), and PVA (polyvinyl alcohol) form a three-dimensional hydrophilic gel polymer on the surface of the ceramsite, which can absorb aqueous liquid without dissolving in the medium. At the same time, the surface area of the filler is greatly increased, providing more surface for microorganisms to attach, enhancing the formation of biofilm, and improving the removal efficiency of pollutants.
[0026] Second, the modified biological filler (MgFe-LDHs-SA-PVA composite ceramsite) provided by the present invention combines a variety of functional materials in structural design compared to ordinary ceramsite, significantly improving the removal efficiency of total nitrogen and other pollutants in wastewater treatment, and its advantages include larger specific surface area, stronger electrostatic attraction, providing carbon source to support microbial growth, enhanced mechanical and chemical stability, initial rapid removal effect and long-term efficient biodegradability. These characteristics make composite ceramsite have broad prospects in practical engineering applications.
[0027] 3. SA is a biopolymer with the characteristics of being non-toxic, biocompatible, biodegradable, and abundant in nature. When the present invention modifies ceramsite, SA is introduced to give the filler excellent biocompatibility. At the same time, when the organic matter content in the water body is insufficient, SA can be used as a carbon source to maintain the activity of microorganisms.
[0028] Fourth, when the present invention modifies ceramsite, the functional materials PVA and SA introduced have a synergistic effect. By adding PVA, the problem of polymer disintegration when SA is consumed can be solved. At the same time, relying on the mechanical properties and high chemical resistance of PVA, the polymer of the outer layer is more stable, reducing the risk of filler breakage and extending the service life. In addition, when the modified biological filler is applied to the BAF biofilter, it can show stronger stability and impact load resistance when the organic matter concentration fluctuates, which can better maintain the normal operation of the BAF biofilter.
[0029] 5. The surface of the biologically modified filler provided by the present invention carries a negative charge, which improves the adsorption capacity of ammonia nitrogen, thereby effectively reducing the ammonia nitrogen concentration in the water body and improving the removal efficiency of total nitrogen in the water body, especially showing excellent treatment effects in low organic matter and high ammonia nitrogen environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The XRD diagrams of ceramsite and the modified biological filler prepared in Example 1;
[0031] Figure 2 FTIR spectra of ceramsite and modified biofiller prepared in Example 1;
[0032] Figure 3 The nitrogen adsorption-desorption curves of ceramsite and the modified biological filler prepared in Example 1;
[0033] Figure 4 The zeta potential diagram of ceramsite and the modified biological filler prepared in Example 1;
[0034] Figure 5 This is a diagram showing the denitrification effect of expanded clay and the modified biological filler prepared in Example 1. DETAILED DESCRIPTION
[0035] The present invention is described in detail below with reference to the accompanying drawings and embodiments, but the present invention can be implemented in many different ways as limited and covered by the claims.
[0036] The present invention provides a method for preparing a modified biological filler, the preparation method comprising the following steps:
[0037] Step 1), preparing MgFe-LDHs powder by coprecipitation method.
[0038] This step includes:
[0039] Step (a), under stirring, respectively adding a first solution and a second solution to deionized water, and controlling the reaction temperature to be 70°C to 80°C, and the pH value to be 9.8 to 10.2, wherein the first solution comprises a magnesium salt and an iron salt, and the molar ratio of magnesium ions to iron ions is 2:(1 to 1.25), and the solute in the second solution is sodium hydroxide and sodium carbonate, wherein the molar concentration ratio of metal ions in the first solution, hydroxide ions in the second solution, and carbonate ions in the second solution is (0.3 to 0.4):(1.8 to 2.2):(0.04 to 0.06).
[0040] Preferably, the molar concentration ratio of the metal ions in the first solution, the hydroxide ions in the second solution and the carbonate ions in the second solution is 0.3:2:0.05.
[0041] Preferably, the molar concentration of metal ions in the first solution is 0.3 mol / L, the molar concentration of hydroxide ions in the second solution is 2 mol / L, and the molar concentration of carbonate ions in the second solution is 0.05 mol / L.
[0042] After the step (b), the dropwise addition is completed, and the aging is continued at 70° C. to 80° C. for 24 h to 30 h. The suspension obtained by aging is filtered, washed, dried, and ground to obtain MgFe-LDHs powder.
[0043] The step (b) further comprises passing the ground MgFe-LDHs powder through a 200-mesh sieve.
[0044] Preferably, the reaction temperature in step (a) is controlled at 70°C.
[0045] Specifically, the aging time can be 24h, 25h, 26h, 27h, etc.
[0046] Preferably, the drying conditions include: a drying temperature of 80° C. to 100° C., and a drying time of 18 h to 24 h.
[0047] More preferably, the drying conditions include: drying temperature of 80° C. and drying time of 18 h.
[0048] Step 2), under stirring and at a preset temperature, adding the MgFe-LDHs powder to the PVA-SA mixed solution, and stirring for a first preset time to obtain a MgFe-LDHs-SA-PVA mixed solution.
[0049] Preferably, the preset temperature is 80°C to 90°C, more preferably, the preset temperature is 80°C.
[0050] Preferably, the first preset time is 8 hours to 12 hours, and more preferably, the first preset time is 10 hours.
[0051] Preferably, the mass ratio of MgFe-LDHs, PVA and SA in the MgFe-LDHs-SA-PVA mixed solution is: (3-7.5): (3-5): (1-2).
[0052] More preferably, the mass ratio of MgFe-LDHs, PVA and SA in the MgFe-LDHs-SA-PVA mixed solution is 5:5:2.
[0053] Preferably, the PVA-SA mixed solution is prepared by the following method: sodium alginate is added to a polyvinyl alcohol solution, wherein the amount of sodium alginate added is 1wt% to 2wt% based on the mass of the polyvinyl alcohol solution, and the mass percentage of polyvinyl alcohol in the PVA-SA mixed solution is 3wt% to 5wt% based on the mass of the PVA-SA mixed solution; wherein the degree of polymerization of polyvinyl alcohol in the polyvinyl alcohol solution is 100,000 to 150,000.
[0054] More preferably, based on the mass of the polyvinyl alcohol solution, the amount of sodium alginate added is 2wt%, and based on the mass of the PVA-SA mixed solution, the mass percentage of polyvinyl alcohol in the PVA-SA mixed solution is 5wt%. The preparation method of the PVA-SA mixed solution can be specifically: 2g of sodium alginate is added to 100g of polyvinyl alcohol solution (5.0wt%) to obtain.
[0055] In the present invention, the addition of SA sodium alginate and PVA polyvinyl alcohol increases the viscosity of the solution. More than 2 wt % of sodium alginate and more than 5 wt % of polyvinyl alcohol will cause the water to be paste-like, making it difficult for powdered MgFe-LDHs to be evenly dispersed in the solution.
[0056] Preferably, based on the mass of the PVA-SA mixed solution, the added amount of the MgFe-LDHs powder is 3% to 7.5%.
[0057] More preferably, based on the mass of the PVA-SA mixed solution, the added amount of the MgFe-LDHs powder is 5%.
[0058] In the present invention, based on the mass of the PVA-SA mixed solution as 100%, adding more than 7.5wt% of MgFe-LDHs powder into the PVA-SA mixed solution will cause the prepared hydrogel to become hard and brittle, thereby losing the elasticity of the hydrogel and being damaged when impacted by hydraulic flow.
[0059] Step 3), immersing the ceramsite in the MgFe-LDHs-SA-PVA mixed solution for 8h to 12h to obtain immersed ceramsite, the mass volume ratio of the ceramsite to the MgFe-LDHs-SA-PVA mixed solution is: 1g: (2-5)ml.
[0060] Preferably, the mass ratio of the ceramsite to the MgFe-LDHs-SA-PVA mixed solution is 1 g:5 ml.
[0061] In the present invention, the ceramsite is a porous ceramic material, and the particle size of the ceramsite is 1 cm to 2 cm.
[0062] Step 4), immersing the immersed ceramsite in a supersaturated boric acid solution containing CaCl2 and NaCl, so that the calcium chloride and SA, as well as the boric acid and PVA, respectively undergo cross-linking reactions, and after the cross-linking reaction is completed, continuing to soak the ceramsite for a second preset time, and after washing, obtaining MgFe-LDHs-SA-PVA composite ceramsite, wherein the MgFe-LDHs-SA-PVA composite ceramsite is a modified biological filler for adsorbing ammonia nitrogen.
[0063] Preferably, the second preset time is 2 hours to 4 hours; more preferably, the second preset time is 3 hours.
[0064] Preferably, the mass volume ratio of the ceramsite to the supersaturated boric acid solution is 1 g: (2-5) ml.
[0065] More preferably, the mass volume ratio of the ceramsite to the supersaturated boric acid solution is 1 g:5 ml.
[0066] Preferably, based on the mass of the supersaturated boric acid solution being 100%, the mass percentage of the calcium chloride is 5wt% to 7.5wt%, and the mass percentage of the sodium chloride is 0.5wt% to 1wt%.
[0067] More preferably, based on the mass of the supersaturated boric acid solution being 100%, the mass percentage of the calcium chloride is 5wt%, and the mass percentage of the sodium chloride is 0.5wt%.
[0068] The invention adopts a coprecipitation method to prepare MgFe-LDHs powder; sodium alginate (SA), polyvinyl alcohol (PVA), MgFe-LDHs powder and ceramsite are mixed, and then cross-linked and encapsulated with calcium chloride and boric acid to obtain MgFe-LDHs-SA-PVA composite ceramsite. Compared with traditional expanded clay, MgFe-LDHs-SA-PVA composite expanded clay has good biocompatibility and can serve as a culture medium for microorganisms. When the content of biodegradable organic matter in the water body is insufficient, SA, as a natural high molecular weight polysaccharide polymer, can serve as a carbon source for microorganisms and maintain the normal operation of the BAF biofilter. The introduction of MgFe-LDHs can enhance the mechanical strength and specific surface area of SA and PVA on the surface of expanded clay. In addition, MgFe-LDHs, as an artificially synthesized clay mineral, can act as a bridge for electron transfer to promote the repair of water bodies by microorganisms. At the same time, the surface Zeta potential of MgFe-SA composite expanded clay is negative, and it shows good adsorption capacity for ammonia nitrogen in water bodies. Applying it to the BAF biofilter can effectively enhance the anti-interference ability and total nitrogen removal efficiency of the BAF biofilter.
[0069] The present invention also provides a modified biological filler, which is prepared by the preparation method of the modified biological filler described above.
[0070] In the present invention, the biological filler includes ceramsite and a three-dimensional hydrophilic gel polymer formed on the surface of the ceramsite by MgFe-LDHs, SA and PVA.
[0071] The present invention also provides the use of the modified biological filler prepared by the preparation method of the modified biological filler described above in wastewater treatment.
[0072] Preferably, the modified raw filler is used in a BAF biofilter to treat wastewater.
[0073] Example 1
[0074] Preparation of modified biological filler (MgFe-LDHs-SA-PVA composite ceramsite)
[0075] The specific steps are as follows:
[0076] Step 1, prepare 500 ml of the first solution and the second solution respectively. Specifically, weigh 51.282 g of Mg(NO3)2·6H2O and 40.398 g of Fe(NO3)3·9H2O and dissolve them in deionized water to obtain the first solution; weigh 40 g of NaOH and 2.65 g of Na2CO3 and dissolve them in deionized water to obtain the second solution.
[0077] Step 2: Use a peristaltic pump to control the titration rate to drip the first solution and the second solution into a three-necked flask filled with deionized water. The three-necked flask is vigorously stirred at a constant temperature of 70° C. in a heat-collecting constant temperature heating magnetic stirrer, and the pH of the solution in the three-necked flask is controlled to maintain 10±0.2.
[0078] Step 3: After the titration is completed, the reaction solution in the three-necked flask is aged at 70° C. for 25 h, and then the suspension is filtered using a circulating water vacuum pump and washed several times with deionized water and alcohol until the pH of the supernatant is neutral.
[0079] Step 4: Dry the filtered product at 80° C. for 20 h, and then grind it through a 200-mesh sieve to obtain MgFe-LDHs powder.
[0080] Step 5: Add 2.0 g of sodium alginate to 100 g of 5.0 wt% polyvinyl alcohol solution to obtain a PVA-SA mixed solution, wherein the degree of polymerization of the polyvinyl alcohol is 143,000.
[0081] Step 6: Add 5 g of MgFe-LDHs powder to the PVA-SA mixed solution prepared in step 1.5, place in a heat-collecting constant temperature heating magnetic stirrer, and stir continuously at 80°C for 10 h to obtain a MgFe-LDHs-SA-PVA mixed solution.
[0082] Step 7: 20 g of ceramsite (average specific surface area 46.83 m 2 / g) was immersed in the MgFe-LDHs-SA-PVA mixed solution prepared in step 6 for 8 hours to obtain immersed ceramsite.
[0083] Step 8, immersing the ceramsite in 100 ml of supersaturated boric acid solution (40 g / L) containing CaCl2 (5 wt%) and NaCl (0.5 wt%), so that the calcium chloride and SA, as well as the boric acid and PVA, undergo cross-linking reactions, and after the cross-linking reaction is completed, continue to immerse the ceramsite for 2 h, and use deionized water for multiple washing to obtain MgFe-LDHs-SA-PVA composite ceramsite, and the composite ceramsite is immersed in deionized water for storage, and the specific surface area of the composite ceramsite is 130.09 m 2 / g.
[0084] It should be noted that the MgFe-LDHs-SA-PVA composite ceramsite is the modified biofiller.
[0085] See also Figure 1 , Figure 1 The XRD patterns of the ceramsite and the modified biofiller prepared in Example 1 are shown in FIG. Figure 1 It can be seen that characteristic peaks (003) and (006) appear on the modified biofiller, which is consistent with the MgFe-LDHs standard card (JCPDS#24-1091), while polysaccharides and high molecular polymers (SA and PVA) will not appear in the XRD spectrum but will cause baseline shift, which is consistent with the XRD spectrum results obtained in the present invention.
[0086] See also Figure 2 , Figure 2 FTIR spectra of ceramsite and modified biofiller prepared in Example 1. Figure 2 It can be seen that the FTIR spectrum shows the presence of -CO- and -CH groups representing polyvinyl alcohol (PVA), -CO-C groups of alginate, and carbonate (CO3 2- ) group; The above results show that the modified biological filler prepared in Example 1 effectively combines the composite materials together and successfully prepares MgFe-LDHs-SA-PVA composite ceramsite.
[0087] See also Figure 3 , Figure 3 The nitrogen adsorption and desorption curves of the ceramsite and the modified biological filler prepared in Example 1 are shown in FIG. Figure 3 It can be seen that the nitrogen adsorption capacity of the modified biological filler prepared in Example 1 is much greater than that of ceramsite. The reason is that the specific surface area of the modified biological filler is 130.09 m 2 / g, much larger than the specific surface area of ceramsite 46.83m 2 / g, indicating that the modified biological filler has a larger specific surface area, can provide stronger adsorption performance and more surface for microorganisms to attach, and enhance the formation of biofilm.
[0088] See also Figure 4 , Figure 4 The zeta potential diagram of the ceramsite and the modified biological filler prepared in Example 1. Figure 4 It can be seen that the modified biological filler has a lower surface charge and a stronger electrostatic attraction to ammonia nitrogen, organic matter, and cationic pollutants, which can effectively improve the removal efficiency of total nitrogen in water bodies.
[0089] Figure 4In the zeta potential diagram, MgFe-LDHs-SA-PVA composite expanded clay has a lower surface charge and a stronger electrostatic attraction to ammonia nitrogen, organic matter, and cationic pollutants, which can effectively improve the removal efficiency of total nitrogen in water bodies.
[0090] Example 2
[0091] Application of ceramsite and modified biological filler prepared in Example 1 in denitrification
[0092] The ceramsite and the modified biological filler prepared in Example 1 were used to treat the actual high-concentration total nitrogen wastewater by natural biofilm formation under non-aeration conditions. The total nitrogen in the water quality was measured according to the standard HJ 636-2012. The denitrification effects corresponding to different times are detailed in Figure 5 .from Figure 5 It can be seen that compared with expanded clay, MgFe-LDHs-SA-PVA composite expanded clay has a removal effect of 14.3% from the first day, which is mainly attributed to the larger surface area and stronger electrostatic attraction of MgFe-LDHs-SA-PVA composite expanded clay. After adsorption saturation, MgFe-LDHs-SA-PVA composite expanded clay can still have a good total nitrogen removal efficiency, and the total nitrogen removal efficiency reaches 86.2% at 24 days (Table 1). At this time, it mainly depends on the removal effect of microorganisms on MgFe-LDHs-SA-PVA composite expanded clay, while the adsorption effect of expanded clay on the first day is only 11%. It was not until the 8th day that the microorganisms began to play a role in total nitrogen removal, and the final total nitrogen removal efficiency was only 64.4%.
[0093] The water quality analysis in denitrification application is detailed in Table 1.
[0094] Table 1 Water quality analysis in denitrification applications
[0095] Water sample name Initial total nitrogen (mg / L) Total nitrogen at the end of the experiment (mg / L) Composite ceramsite 130 18 Clay 118 42
[0096] Example 3
[0097] The ceramsite and the modified biological filler prepared in Example 1 were used to treat a certain landfill leachate.
[0098] The ceramsite and the modified biological filler prepared in Example 1 were used as fillers of a BAF biofilter, respectively. The BAF biofilter was then used to treat a certain landfill leachate. The BAF effluent results were measured according to standard HJ 636-2012. The measurement results are shown in Tables 2 and 3, wherein Table 2 is the BAF effluent results of the ceramsite, and Table 3 is the BAF effluent results of the modified biological filler prepared in Example 1.
[0099] Table 2 effluent results of ceramsite BAF
[0100] Water sample name TN(mg / L) Fenton Water 69.9 BAF water outlet 23.7
[0101] Table 3 MgFe-LDHs-SA-PVA composite ceramsite BAF effluent results
[0102] Water sample name TN(mg / L) Fenton Water 77.7 BAF water outlet 17.7
[0103] Comparing the data in Table 2 and Table 3, it can be seen that the total nitrogen treatment efficiency of MgFe-LDHs-SA-PVA composite ceramsite (77%) is greatly improved compared with that of plain ceramsite (66%).
[0104] The modified biological filler prepared in Example 1 of the present invention is applied to the treatment of a certain landfill leachate, which has the advantages of stable and reliable effluent water quality and strong impact resistance, and can meet the standards of Table 2 of "Control of Pollutants in Municipal Waste Landfills" (GB16889-2024).
[0105] Comparative Example 1
[0106] Step 1, prepare 500 ml of 1 mol / L AlCl3 metal salt solution;
[0107] Step 2, putting the ceramsite into the AlCl3 metal salt solution prepared in step 1, immersing and ultrasonicating for 1 to 2 hours, drying at 100°C for 6 hours, and then sintering at 550°C for 5 hours in a muffle furnace to obtain sintered ceramsite;
[0108] Step 3: After the sintered ceramsite is naturally cooled, wash it, and dry it at 100° C. for 3 h to obtain dry sintered ceramsite.
[0109] Step 4: Add 2.0 g of sodium alginate to 100 g of a 5.0 wt% polyvinyl alcohol solution to obtain a PVA-SA mixed solution, wherein the degree of polymerization of the polyvinyl alcohol is 143,000.
[0110] Step 5: Add 20 g of sintered ceramsite into the PVA-SA mixed solution, place the mixed solution in a heat-collecting constant temperature heating magnetic stirrer, and stir continuously at 80° C. for 8 h to obtain immersed ceramsite.
[0111] Step 6: Immerse the immersed ceramsite in 100 ml of supersaturated boric acid solution containing CaCl2 (5 wt%) and NaCl (0.5 wt%) to cause a cross-linking reaction. After the cross-linking reaction is completed, the ceramsite is further immersed in the cross-linking agent for 2 h. After the immersion is completed, it is washed several times with deionized water to obtain AlCl3-SA-PVA sintered ceramsite. The AlCl3-SA-PVA sintered ceramsite is immersed in deionized water for storage. The specific surface area of the AlCl3-SA-PVA sintered ceramsite is 67.21 m 2 / g.
[0112] The AlCl3-SA-PVA sintered ceramsite treated in this example has less surface load and is easy to fall off. During the cross-linking process, some Al ions on the surface of the ceramsite will react with SA first to form aluminum alginate gel, thereby affecting the subsequent cross-linking of the sintered ceramsite with PVA and boric acid, making it difficult to form a double cross-linked network of the hydrogel, reducing the stability of the ceramsite surface.
[0113] Compared with Example 1, Comparative Example 1 differs in that MgFe-LDHs is used instead of Al oxide. The present invention makes MgFe-LDHs into powder and melts it into the SA-PVA mixed solution, which can increase the loading amount on the surface of the ceramsite from the original milligram level to the gram level, greatly increasing the loading amount on the surface of the ceramsite; at the same time, the double cross-linked network of SA and PVA is guaranteed to enhance the stability of the material; at the same time, Mg and Fe exist in large quantities in the environment, and are also necessary elements for the growth and reproduction of microorganisms and plants. Compared with Al ions (which have certain Al toxicity to microorganisms and plants), the biological toxicity of metal ions is reduced.
[0114] Comparative Example 2
[0115] Comparative Example 2 is the same as Comparative Example 1, except that FeCl3 is used instead of AlCl3 in Comparative Example 2 to prepare FeCl3-SA-PVA sintered ceramsite with a specific surface area of 52 m 2 / g.
[0116] The FeCl3-SA-PVA sintered ceramsite prepared in Comparative Example 2 has a small surface loading. When the ceramsite is immersed in a FeCl3 solution, only a small amount of Fe can be adsorbed on the surface of the ceramsite through physical adsorption and micropore adsorption in the pores of the ceramsite. After calcination, iron oxide is loaded on the ceramsite, and then PVA and SA hydrogel are formed on the surface of the ceramsite.
[0117] Comparative Example 2 is different from Example 1 in that MgFe-LDHs is used instead of Fe oxide. The present invention makes MgFe-LDHs into powder and melts it into SA-PVA mixed solution, which can increase the load on the surface of ceramsite from the original milligram level to the gram level, greatly increasing the load on the surface of ceramsite; and the increase in the load of MgFe-LDHs doubles the specific surface area of ceramsite, as shown in Table 4; compared with iron oxide, MgFe-LDHs has better adsorption performance and can adsorb organic matter, heavy metal ions, dye molecules, etc. in the solution, and hydrotalcite has high stability, so that hydrotalcite has wide potential for application in various fields. Hydrotalcite has a layered structure, which makes its crystals difficult to decompose under normal conditions, which makes its recycling performance more improved.
[0118] Table 4 BET analysis of the composite ceramsite prepared in Example 1 and the sintered ceramsite prepared in Comparative Example 2
[0119] name <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[Pore volume (cm 3 / g)]]> MgFe-LDHs-SA-PVA composite ceramsite 130.09 0.291 <![CDATA[FeCl3-SA-PVA sintered ceramsite]]> 52.00 0.255
[0120] Combining the data and drawings of the embodiments, it can be seen that:
[0121] 1. The MgFe-LDHs-SA-PVA composite ceramsite provided by the present invention has a larger specific surface area than ordinary ceramsite and the sintered ceramsite prepared in Comparative Examples 1 and 2. On the one hand, the larger specific surface area can provide more active sites, enhance the adsorption capacity of ceramsite for pollutants (such as ammonia nitrogen, heavy metal ions, etc.), that is, improve the pollutant removal effect; on the other hand, the larger specific surface area can provide attachment space for more microorganisms, which is conducive to the rapid formation of biofilm, thereby improving the wastewater treatment efficiency.
[0122] 2. The MgFe-LDHs-SA-PVA composite ceramsite provided by the present invention has a stronger negative charge on its surface. + ) and some organic pollutants are positively charged, and the negative charge on the surface of expanded clay will enhance the electrostatic adsorption capacity of these pollutants, thereby improving the removal efficiency of pollutants.
[0123] 3. After Fenton catalytic oxidation, the wastewater enters the BAF biological filter. At this time, the bioavailable COD content in the wastewater is low, and additional carbon sources need to be added. The SA (alginate) and PVA (polyvinyl alcohol) in the MgFe-LDHs-SA-PVA composite expanded clay have the following advantages: SA, as a natural polysaccharide, can be decomposed into biodegradable carbon sources during microbial metabolism, thereby supporting the growth of microorganisms under low organic matter concentrations, maintaining microbial activity, and improving the total nitrogen removal efficiency; SA and PVA have good biocompatibility and will not cause adverse effects on microorganisms in the water body. Instead, they help promote the growth and reproduction of microorganisms and enhance the formation speed and stability of biofilms.
[0124] 4. The MgFe-LDHs-SA-PVA composite ceramsite provided by the present invention has a strong initial adsorption effect, thanks to its large specific surface area and electrostatic attraction ability. Compared with traditional ceramsite, the composite ceramsite can quickly adsorb ammonia nitrogen and other pollutants before adsorption saturation. At the same time, after the adsorption tends to saturation, the composite ceramsite provides a more favorable growth environment for microorganisms and forms a stable biofilm, thereby continuously and efficiently degrading pollutants such as total nitrogen during long-term operation.
[0125] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions and substitutions can be made without departing from the concept of the present invention, which should be regarded as belonging to the protection scope of the present invention.
Claims
1. A method for preparing a modified biological filler, characterized in that: The preparation method comprises the following steps: Step 1), preparing MgFe-LDHs powder by coprecipitation method; Step 2), under stirring and at a preset temperature, adding the MgFe-LDHs powder to the PVA-SA mixed solution, and stirring for a first preset time to obtain a MgFe-LDHs-SA-PVA mixed solution; Step 3), immersing the ceramsite in the MgFe-LDHs-SA-PVA mixed solution for 8h~12h to obtain immersed ceramsite, wherein the mass volume ratio of the ceramsite to the MgFe-LDHs-SA-PVA mixed solution is: 1g: (2~5)ml; Step 4), immersing the immersed ceramsite in a supersaturated boric acid solution containing calcium chloride and sodium chloride, so that the calcium chloride and SA, and the boric acid and PVA respectively undergo cross-linking reactions, and after the cross-linking reaction is completed, continuing to soak the ceramsite for a second preset time, and after washing, obtaining MgFe-LDHs-SA-PVA composite ceramsite, wherein the MgFe-LDHs-SA-PVA composite ceramsite is the modified biological filler for adsorbing ammonia nitrogen.
2. The method for preparing the modified biological filler according to claim 1, characterized in that: The step 1) comprises: Step (a), under stirring, respectively adding a first solution and a second solution to deionized water, and controlling the reaction temperature to be 70°C-80°C, and the pH value to be 9.8-10.2, wherein the first solution comprises a magnesium salt and an iron salt, and the molar ratio of magnesium ions to iron ions is 2:(1-1.25), and the solute in the second solution is sodium hydroxide and sodium carbonate, wherein the molar concentration ratio of metal ions in the first solution, hydroxide ions in the second solution, and carbonate ions in the second solution is (0.3-0.4):(1.8-2.2):(0.04-0.06); After the step (b), the temperature is kept at 70° C. to 80° C. for 24 h to 30 h, and the suspension obtained by aging is filtered, washed, dried and ground to obtain MgFe-LDHs powder.
3. The method for preparing the modified biological filler according to claim 2, characterized in that: In step (b), the drying conditions include: drying temperature of 80° C. to 100° C., and drying time of 18 h to 24 h.
4. The method for preparing the modified biological filler according to claim 1, characterized in that: In step 2), the preset temperature is 80°C to 90°C.
5. The method for preparing the modified biological filler according to any one of claims 1 to 4, characterized in that: In step 2), the mass ratio of MgFe-LDHs, PVA and SA in the MgFe-LDHs-SA-PVA mixed solution is: (3-7.5): (3-5): (1-2).
6. The method for preparing the modified biological filler according to claim 5, characterized in that: In step 2), the PVA-SA mixed solution is prepared by the following method: sodium alginate is added to a polyvinyl alcohol solution, wherein the amount of sodium alginate added is 1wt%~2wt% based on the mass of the polyvinyl alcohol solution; the mass percentage of polyvinyl alcohol in the PVA-SA mixed solution is 3wt%~5wt% based on the mass of the PVA-SA mixed solution; wherein the degree of polymerization of polyvinyl alcohol in the polyvinyl alcohol solution is 100,000~150,000.
7. The method for preparing the modified biological filler according to claim 1, characterized in that: In step 2), the first preset time is 8 hours to 12 hours, and in step 4), the second preset time is 2 hours to 4 hours.
8. The method for preparing the modified biological filler according to claim 1, characterized in that: In step 4), based on the mass of the supersaturated boric acid solution being 100%, the mass percentage of the calcium chloride is 5wt% to 7.5wt%, and the mass percentage of the sodium chloride is 0.5wt% to 1wt%.
9. A modified biological filler, characterized in that: The modified biological filler is prepared by the preparation method of the modified biological filler according to any one of claims 1 to 8.
10. Use of the modified biological filler prepared by the preparation method of the modified biological filler according to any one of claims 1 to 8 in wastewater treatment.